Analisis Kelayakan Teknis dan Ekonomi Rekayasa Pembangunan Jalan Tol Seksi X Menggunakan Metode Life Cycle Cost - Anugrah Heris Santri; Rezi Munizar; Hendret Susanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The imbalance between traffic volume growth and road infrastructure capacity has intensified congestion, reduced logistics efficiency, and increased emissions along urban and intercity transport corridors. This study evaluates the technical and engineering-economic feasibility of the proposed 15.5 km Section X Toll Road using the Life Cycle Cost (LCC) approach. An empirical quantitative method was employed by integrating road capacity analysis, geometric design, rigid pavement design, and investment evaluation using Net Present Value (NPV), Internal Rate of Return (IRR), Benefit–Cost Ratio (BCR), and Payback Period (PP) indicators. The results indicate that the proposed toll road reduces the degree of saturation of the existing arterial road from 0.85 to 0.42. Economic evaluation produced a positive NPV of IDR 542 billion, an IRR of 12.45%, a BCR of 1.18, and a payback period of 14 years and 3 months. Sensitivity analysis confirms that the project remains financially feasible under a 15% increase in construction costs and a 10% decline in toll revenue. These findings demonstrate that the Section X Toll Road is technically feasible, economically viable, and capable of supporting sustainable infrastructure investment.